Nitric oxide reversibly binds the reduced [2Fe-2S] cluster in mitochondrial outer membrane protein mitoNEET and inhibits its electron transfer activity - Fontenot, Chelsey R.; Cheng, Zishuo; Ding, Huangen (Frontiers in Molecular Biosciences, 2022)
MitoNEET is a mitochondrial outer membrane protein that regulates energy metabolism, iron homeostasis, and production of reactive oxygen species in cells. Aberrant expression of mitoNEET in tissues has been linked to type II diabetes, neurodegenerative diseases, and several types of cancer. Structurally, the N-terminal domain of mitoNEET has a single transmembrane alpha helix that anchors the protein to mitochondrial outer membrane. The C-terminal cytosolic domain of mitoNEET hosts a redox active [2Fe-2S] cluster via an unusual ligand arrangement of three cysteine and one histidine residues. Here we report that the reduced [2Fe-2S] cluster in the C-terminal cytosolic domain of mitoNEET (mitoNEET45-108) is able to bind nitric oxide (NO) without disruption of the cluster. Importantly, binding of NO at the reduced [2Fe-2S] cluster effectively inhibits the redox transition of the cluster in mitoNEET45-108. While the NO-bound [2Fe-2S] cluster in mitoNEET45-108 is stable, light excitation releases NO from the NO-bound [2Fe-2S] cluster and restores the redox transition activity of the cluster in mitoNEET45-108. The results suggest that NO may regulate the electron transfer activity of mitoNEET in mitochondrial outer membrane via reversible binding to its reduced [2Fe-2S] cluster.